The Prevalence of Uraemic Pruritus and its Association With Some Biochemical & Hematological Parameters in hemodialysis patients from Misurata City-Libya - Mohamed A. Alghazal, Almahdi M. Aljady, Amal M. Karyem, Zeyad M.Eldenfiria (Journal of Pure & Applied Sciences, 2020)
The aim of the present study was to investigate the prevalence of uraemic pruritus among hemodialysis patients from Misurata city, and to evaluate its possible association with some clinical symptoms, biochemical & hematological parameters as well as blood group types. One hundred and seventy dialysis-treated patients attended the hemodialysis center of Misurate city were included in this study; they were aged between 20 -80 years, during the period from February to March 2017. In addition to the investigation of clinical symptoms, blood samples from each patient were subjected to some biochemical tests: (AST, ALT, ALK, Creatinine, Urea, Uric acid, Total protein, Albumin, Mg++، S-Ca++, Iron, Phos, PTH), and to complete blood count (CBC). Data showed that 60.59% of the included patients had uraemic pruritus; Of whom, 22.33%, 49.51%, and 28.16% had mild, moderate, and sever uraemic pruritus respectively. The obtained data also indicated that psychiatric status, sleep disturbances, skin dryness, and drug used for the treatment of kidney failure had a significant positive correlation with the uraemic pruritus ( P = 0.021, ˂0.00, ˂0.00, ˂0.00 respectively). However, MCHC and MCH had a significant negative correlation with the uraemic pruritus (P= 0.01, 0.02 respectively). On the other hand gender, biochemical parameters, and other hematological parameters had no significant correlation with the uraemic pruritus (P ˃ 0.05). The prevalence of uraemic pruritus according the blood group type and rhesus factor was as follows: group AB 78.95%, group B 63.64%, group O 61.67% then group A 53.63%; Rhesus factor was equally distributed (approximately 60% for each of the +ve and the –ve type).In conclusion, results reported herein showed a high prevalence of Uraemic pruritus among the study population, which was correlated to some clinical characteristics such as psychiatric status, sleep disturbances, skin dryness, and drug used for the treatment of kidney failure, and also with some hematological parameters such as MCHC, MCH, and blood group type; however all of the biochemical parameters showed no correlation with the prevalence of Uraemic pruritus.